Thermodynamic and kinetics considerations in the competition between the dye regeneration and the recombination process in dye-sensitized solar cells - Ávila, Mauricio; Cerdá, María Fernanda (Frontiers in Coatings, Dyes and Interface Engineering, 2025)
Dye-sensitized solar cells comprise a fluorine doped tin oxide/titanium dioxide photoanode and a counter electrode of fluorine doped tin oxide covered with a catalytic material arranged in a sandwich configuration. Many processes take place inside a dye-sensitized solar cell. However, two involve the redox couple contained in the electrolyte solution: the dye regeneration and the recombination. While the first is a desired path, the latter impacts the power conversion efficiency of the cells, decreasing the measured values. In this work, iodine-based couples are evaluated using cyclic voltammetric measurements, and their behaviour is compared with two commercial electrolytes widely used in dye-sensitized solar cells, particularly when sensitized with natural dyes. Different experimental conditions, such as cell configurations and electrode materials, were adopted to understand the thermodynamics of the competitive electron transfer processes mentioned above.